The Pittsburg Project: Graduate Community/Urban Design-Historic Preservation Studio - James McCullar (Oz, 1981)
Project Development. Pittsburg is a city of 20,000 people in southeastern Kansas. In a period of renewed economic activity, Pittsburg had begun to face physical growth problems now becoming familiar to many small urban centers across America…